Pendampingan Perumusan Strategi Pengembangan Usaha pada UMKM Saung Granit Menggunakan Pendekatan SWOT, IFE, dan EFE - Risna Ananda Aryani; Keysha Valloma Fardhaniati Putriku; Frili Asia Musfrida; Stella Valencia Kurniawan; Refina Hilda Pratiwi; Ridlwan Muttaqin (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting national economic growth. However, increasing business competition requires MSME actors to implement appropriate strategies to sustain and develop their businesses. This community service activity aimed to assist Saung Granit MSME in formulating business development strategies based on an analysis of the company's internal and external conditions. The assistance process involved observation, interviews, and documentation. Strategic analysis was conducted using the Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, and SWOT Analysis. The results of the assistance indicated that Saung Granit MSME possesses favorable internal and external conditions to support business growth. Based on the Internal–External (IE) Matrix analysis, Saung Granit MSME is positioned in the Growth Stability (Quadrant V) category. Therefore, the recommended strategies include strengthening digital marketing, enhancing business branding, expanding cooperation networks, and improving customer service quality. Through this assistance program, Saung Granit MSME is expected to improve its competitiveness and achieve sustainable business development